Implementasi Program Ekopesantren di Pondok Pesantren Madinatunnajah, Cilimus - Rahmadiani, Mutiara Nurul; Mangunjaya, Fachruddin Majeri; Zulham, Muhammad (Himmah: Jurnal Kajian Islam Kontemporer, 2024)
Islamic boarding schools are synonymous with environmental management which tends to be weak because most of the environmental management still uses traditional techniques. In the MBKM PPI Unas Ecopesantren program, there are various ways to provide information, da'wah training, lectures on biodiversity and how to play a role in protecting nature and the environment. This eco-pesantren has ten programs, namely environment-based curriculum programs, integration of environmental fiqh lessons, improvement of human resources, pesantren land, water resources, healthy living, waste and garbage, energy, transportation, and biodiversity. The implementation of Ecopesantren activities at the Madinatunnajah Islamic boarding school, Cilimus, namely, environment-based curriculum programs, biodiversity, healthy living, and waste and waste management. The mission of this project is to realize an environmentally friendly pesantren. The existence of the Ecopesantren program is an effort to help the boarding school community to protect and conserve the surrounding environment. Keywords: Ecopesantren, Environmental Management, Nature and Environment